2048-Point FFT Core Generator for Digital Video Broadcasting (DVB) - T. Hithaishi Mohan, Shilpa J, Prashant V. Joshi, K. M. Sudharshan (International Journal of Advanced Science and Technology, 2020)
A pipelined 2048 point FFT and its inverse processor is proposed based on Radix-2 decimation in frequency FFT butterfly. The butterfly is the primary component of the design. The Radix-2 DIF FFT is based on Cooley-Tukey algorithm. This portrays the technique for the usage of FFT for OFDM applications like digital video broadcasting. The FFT plays a vital role in the design of OFDM. The system uses IFFT for modulation at transmitter and FFT for demodulation at receiver side. The main goal of this proposed work is to perform static timing analysis on the design to get better operating frequency and also to reduce the power consumption. Hence, the design is synthesized and analyzed using Xilinx Vivado tool targeted for Virtex-7. Keywords: FFT Core, FPGA, OFDM, Radix-2, Static Timing Analysis